2007
DOI: 10.1083/jcb.200703010
|View full text |Cite
|
Sign up to set email alerts
|

Contact-dependent inhibition of EGFR signaling by Nf2/Merlin

Abstract: The neurofibromatosis type 2 (NF2) tumor suppressor, Merlin, is a membrane/cytoskeleton-associated protein that mediates contact-dependent inhibition of proliferation. Here we show that upon cell–cell contact Merlin coordinates the processes of adherens junction stabilization and negative regulation of epidermal growth factor receptor (EGFR) signaling by restraining the EGFR into a membrane compartment from which it can neither signal nor be internalized. In confluent Nf2 −/− cells, EGFR activation persists, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
345
3
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 327 publications
(366 citation statements)
references
References 64 publications
16
345
3
2
Order By: Relevance
“…Merlin has been proposed to suppress proliferation by reducing the amount of transmembrane growth factor receptors at the plasma membrane [22,74,75]. Genetic analysis in Drosophila showed that Merlin, cooperating with the FERM domain protein Expanded, promotes endocytosis of several transmembrane receptors, including some involved in mitogenic signalling [75].…”
Section: Inhibition Of Receptor Tyrosine Kinase Activationmentioning
confidence: 99%
“…Merlin has been proposed to suppress proliferation by reducing the amount of transmembrane growth factor receptors at the plasma membrane [22,74,75]. Genetic analysis in Drosophila showed that Merlin, cooperating with the FERM domain protein Expanded, promotes endocytosis of several transmembrane receptors, including some involved in mitogenic signalling [75].…”
Section: Inhibition Of Receptor Tyrosine Kinase Activationmentioning
confidence: 99%
“…EBP50 silencing elicits EMT-associated features through EGFR activation EBP50 acts as a linker between F-actin-binding molecules and cell junctional proteins (for example, b-catenin), and thereby presumably participates in cell adhesion (Curto et al, 2007;Kreimann et al, 2007). We tested whether this mechanism involves EGFR.…”
Section: Ebp50 Silencing Increases Egfr Expression and Downstream Sigmentioning
confidence: 99%
“…Therefore, our findings suggest that EBP50 may contribute to the E-cadherin/b-catenindependent intercellular adhesion by acting directly on EGFR signaling output. Curto et al (2007) demonstrated that merlin/Nf2 tethers EBP50 to the cell cytoskeleton (Murthy et al, 1998) and thereby participates in the stabilization of AJs through the regulation of EGFR. The observation that EBP50, but not merlin/ Nf2, interacts directly with EGFR (Lazar et al, 2004;Takahashi et al, 2006;Curto et al, 2007), suggests that EBP50 regulates EGFR signaling per se.…”
Section: Loss Of Ebp50-egfr Interplay In Biliary Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Nf2 inactivation results in destabilization of adherens junctions (AJs) that are essential for contact inhibition of proliferation in mouse embryonic fibroblasts (MEFs) (Lallemand et al, 2003). In addition, merlin can block ligandinduced epidermal growth factor receptor internalization and signaling in various cell types (Curto et al, 2007). In a rat schwannoma cells, merlin also inhibits growth by promoting platelet-derived growth factor receptor (PDGFR) degradation (Fraenzer et al, 2003).…”
Section: Introductionmentioning
confidence: 99%